Consumer price behaviour in Italy: evidence from micro CPI data - Giovanni Veronese; Silvia Fabiani; Angela Gattulli; Roberto Sabbatini (European Central Bank (ECB), 2005)
This paper investigates the behaviour of consumer prices in Italy by looking at micro data in the attempt to obtain a quantitative measure of the unconditional degree of price rigidity in the Italian economy. The analysis focuses on the monthly frequency of price changes and on the duration of price spells, also with reference to different types of products and outlets. Prices tend to remain unchanged on average for around 10 months; duration is longer for nonenergy industrial goods and services and much shorter for energy products. Price changes are more frequent upward than downward, in larger stores than in traditional ones. When the geographical location of outlets is accounted for, price changes display considerable synchronisation, in particular in the service sector.
Keywords: D21; D40; E31; 330; consumer prices; frequency of price change; nominal rigidity; Konsumentenverhalten; Verbraucherpreisindex; Italien